Testing the Psychometric Properties of the Managing the Emotions of Others Scale - Gözde Uysal; Handan Alan (Association of Nurse Managers, 2023)
Introduction: Managing the emotions of others involves understanding and manipulating their emotions effectively. Nurses who can manage the emotions of others can communicate and interact with patients and their relatives more satisfactorily, thus increasing the quality of care and patient satisfaction. Aim: This study aims to determine the validity and reliability of the Turkish version of the Managing the Emotions of Others Scale (MEOS). Method: The data were collected from 406 nurses from three hospitals, including one university, one public, and one private hospital. The scale was translated into Turkish in accordance with the World Health Organization guidelines. Content validity, construct validity, test-retest reliability, and internal consistency analyses were performed. Results: Following the language and content validity of the scale was performed, its construct validity was assessed. The Turkish version of the MEOS retained its original 6-factor structure. The EFA factor loadings varied between 0.36 and 0.72. The CFI goodness-of-fit indices were as follows: χ2 = 2442.940, df = 1104, RMSEA = 0.055, GFI = 0.81, CFI = 0.88 and IFI = 0.90. The internal consistency coefficient varied between 0.81 and 0.93 for the subscales. Conclusion: The MEOS_TR is a valid and reliable measurement tool for Turkish nurses.